2022 9th IEEE RAS/EMBS International Conference for Biomedical Robotics and Biomechatronics (BioRob) 2022
DOI: 10.1109/biorob52689.2022.9925318
|View full text |Cite
|
Sign up to set email alerts
|

Soft Control Interface for Highly Dexterous Unilateral Remote Palpation

Abstract: Achieving telepresence is the biggest challenge preventing healthcare robotics to permeate the field of primary care and performing tasks such as remote palpation. To do so, the user interface is of fundamental importance: ideally, it would reproduce similar conditions to the in-person task, resulting in intuitive and natural. Many studies focused on the high fidelity of the haptic and tactile feedback, overlooking the importance of the control interface. On the other hand, stateof-the-art soft control interfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…u(•) is the step function and v 0 is a constant speed selected to be 20 mm/s. For the participants' study, the threshold values θ 0 and θ 1 have been selected as 0.09 and 0.01, respectively, based on previous studies of such technology 38 .…”
Section: Soft Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…u(•) is the step function and v 0 is a constant speed selected to be 20 mm/s. For the participants' study, the threshold values θ 0 and θ 1 have been selected as 0.09 and 0.01, respectively, based on previous studies of such technology 38 .…”
Section: Soft Controlmentioning
confidence: 99%
“…However, all reported cases of bilateral physical twins either have extremely limited degrees of freedom (DoFs) or have solely been tested in simulation and not in a real leader-follower architecture. Recently, Costi et al 38 , have demonstrated how it is possible to use barometric sensors in a silicone interface to achieve precise dexterous control of up to 5 DoFs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation